Pemodelan Sebaran Pencemaran Tumpahan Minyak di Perairan Cilacap - Wibowo, Mardi (Jurnal Teknologi Lingkungan, 2018)
ABSTRACTThe Cilacap coastal area plays an important role in recreation, transportation, energy, education or research, residential, and industry. It is also potential for development and potential for pollution especially for oil pollution. That is caused Cilacap has the refinary oil plant and the great port of oil, furthermore it has crowded traffic of ship (both big ship or fishing ships). All of which have a tremendous potential pollute the sea and the surrounding areas. Therefore, it’s needed study of oil slick spreading that caused oil spill to formulate early warning and protection action plan for Cilacap coastal area. This study use oil spill model from DHI (Danish Hydraulic Institute) and use software MIKE-21 modul Particle/Spill Analysis. At each scenario, direction and concentration of oil spill is highly varied, its depend on the hydrodynamic condition o sea water. In January the oil spill from the 70 area pier tends to spread upstream S, Donan and around P. Nusakambangan with slick thickness between 0.0001-2.1 mm and oil spill from SPM spread out south of the model domain. In September the oil spill in the 70 area dock spreads upstream of S Donan with slick thickness between 0.001-2.7 mm and oil spills in SPM spread evenly throughout Cilacap waters with slick thickness between 0.001 to 1 mm. The result of this study is very important to plan early warning system and reduce environmental impact of oil spill. Based on comparation tide model data to tide data from field measuring, its known that both of data has no significance differences.Keywords: oil spill spreading, computational modeling, hydrodynamicsABSTRAKKawasan pesisir Cilacap memiliki potensi pengembangan wilayah yang sangat besar. Namun demikian, kawasan ini juga mempunyai ancaman terhadap pencemaran tumpahan minyak, terutama disebabkan oleh aktivitas kapal, kebocoran pipa, single point mooring (SPM), dan kapal nelayan yang dapat merusak ekosistem perairan Cilacap dan sekitarnya. Karena itu, kajian persebaran minyak diperlukan untuk menyusun tindakan peringatan dini dan perlindungan kawasan pesisir Cilacap. Dalam kajian ini dilakukan pemodelan penyebaran minyak dengan menggunakan model tumpahan minyak dari DHI (Danish Hydraulic Institute) dan perangkat lunak MIKE-21 modul Particle/Spill Analysis. Berbagai parameter inputan data diperoleh dari data sekunder dan hasil survei lapangan pada 8-14 Januari dan 10 16 September 2012. Terdapat empat model skenario penyebaran disusun dan hasil akhir divalidasi dengan hasil pengukuran. Sebagai hasil, arah persebaran dan konsentrasi tumpahan minyak untuk tiap skenario sangat bervariasi dari waktu ke waktu tergantung pada kondisi hidrodinamika perairan yang ada. Pada bulan Januari tumpahan minyak dari dermaga area 70 cenderung menyebar ke hulu S. Donan dan di sekitar P. Nusakambangan dengan ketebalan slick antara 0,0001-2,1 mm dan tumpahan minyak dari SPM tersebar ke selatan keluar ari domain model. Pada bulan September tumpahan minyak di dermaga area 70 tersebar ka arah hulu S Donan dengan ketebalan slick antara 0,001-2,7 mm dan tumpahan minyak di SPM tersebar merata ke seluruh wialayah perairan Cilacap dengan ketebalan slick antara 0,001- 1 mm. Hasil kajian ini sangat penting sebagai dasar perencanaan upaya peringatan dini tumpahan minyak dan meminimalisasi dampak tumpahan minyak. Validasi data pasang surut hasil pemodelan dan pengukuran lapangan dari Intergovernmental Oceanographic Commission (IOC) menunjukkan tidak adanya perbedaan yang nyata.Kata kunci: persebaran tumpahan minyak, pemodelan komputasi, hidrodinamika